Systematic review of mydriatics used for screening of retinopathy in premature infants - Lisa Jean Kremer; David M Reith; Natalie Medlicott; Roland Broadbent (BMJ Publishing Group, 2019)
Introduction Routine retinopathy of prematurity eye examinations are an important part of neonatal care, and mydriatic medicines are essential in dilating the pupil for the eye examination. There are concerns about the level of evidence for efficacy and safety of these mydriatic medicines.Objective This review evaluates both efficacy and safety evidence of mydriatics used during the retinopathy of prematurity eye examination.Method Systematic literature review.Results There is limited evidence guiding clinical practice for safety and efficacy of mydriatics. The majority of publications are underpowered and with an unclear to high level of bias. There are a wide variety of mydriatic regimens evaluated for efficacy and safety, and multiple regimens are associated with case reports.Conclusions Current international guideline seems unnecessarily high, especially when the reviewed literature suggest that lower doses are effective, albiet from underpowered studies. The lowest effective combination regimen appears to be phenylephrine 1% and cyclopentolate 0.2% (1 drop). Microdrop administration of this regimen would further increase the safety profile, however, efficacy needs to be assessed.